Effectiveness of Multicomponent Programs with Community Mobilization for Reducing Alcohol-Impaired Driving - Shults, Ruth A.; Elder, Randy W.; Nichols, James L.; Sleet, David A.; Compton, Richard; Chattopadhyay, Sajal K. (American journal of preventive medicine, 2009)
A systematic review was conducted to determine the effectiveness and economic efficiency of multicomponent programs with community mobilization for reducing alcohol-impaired driving. The review was conducted for the Guide to Community Preventive Services ( Community Guide). Six studies of programs qualified for the review. Programs addressed a wide range of alcohol-related concerns in addition to alcohol-impaired driving. The programs used various crash-related outcomes to measure their effectiveness. Two studies examined fatal crashes and reported declines of 9% and 42%; one study examined injury crashes and reported a decline of 10%; another study examined crashes among young drivers aged 16–20 years and reported a decline of 45%; and one study examined single-vehicle late-night and weekend crashes among young male drivers and reported no change. The sixth study examined injury crashes among underage drivers and reported small net reductions. Because the actual numbers of crashes were not reported, percentage change could not be calculated. According to Community Guide rules of evidence, the studies reviewed here provided strong evidence that carefully planned, well-executed multicomponent programs, when implemented in conjunction with community mobilization efforts, are effective in reducing alcohol-related crashes. Three studies reported economic evidence that suggests that such programs produce cost savings. The multicomponent programs generally included a combination of efforts to limit access to alcohol (particularly among youth), responsible beverage service training, sobriety checkpoints or other well-defined enforcement efforts, public education, and media advocacy designed to gain the support of both policymakers and the general public for reducing alcohol-impaired driving.